Redescription of Dicranoses capsulifex Kieffer and Jörgensen (Lepidoptera: Cecidosidae) with description of the immature stages and biology - Blas, German San; Davis, Donald R. (Zootaxa, 2013)
Dicranoses capsulifex Kieffer and Jörgensen (Lepidoptera: Cecidosidae) is a gall inducing moth associated with Schinus fasciculatus (Griseb.) (Anacardiaceae), with a known distribution restricted to Argentina. It undergoes a one year life cycle (univoltine), with leaf-like galls, and adult with only a half day life span. Male, female, pupa, and gall are redescribed, and the genitalia of both sexes, larva, and life cycle are described herein for the first time using light and scanning electron microscopy. The life cycle is documented from samples consisting of 15 larvae and/or pupae taken every 15 days during the year (from July, 2011, to July, 2012).